2003
DOI: 10.1046/j.1440-1614.2003.01125.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Catatonia in Children and Adolescents in a Paediatric Psychiatric Clinic

Abstract: This study shows that catatonia occurs in children and adolescents. Further studies are essential to clarify the distribution of catatonia across various diagnoses and the outcome of paediatric catatonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(26 citation statements)
references
References 12 publications
3
22
0
1
Order By: Relevance
“…This hypothesis was verified since the entire study group had presented many lifetime catatonic features. This finding is in line with the previous studies by Thakur et al [13] and Green et al [14]. …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This hypothesis was verified since the entire study group had presented many lifetime catatonic features. This finding is in line with the previous studies by Thakur et al [13] and Green et al [14]. …”
Section: Discussionsupporting
confidence: 94%
“…However, despite that catatonia also occurs among children and adolescents [12], it has been sparsely studied among this age group. In a study by Thakur et al [13], 17.7% of the children and adolescents who suffered from affective and non-affective psychotic disorders showed at least two signs of catatonia. Green et al [14] reported that 31.6% of 38 hospitalized children with schizophrenia manifested catatonic features.…”
Section: Introductionmentioning
confidence: 99%
“…It is most commonly associated with mood disorder. 2 Other psychiatric conditions that should be considered are schizophrenia and pervasive developmental disorder. Neurological conditions like seizure disorder, juvenile Parkinson disease, metabolic disorders, and psychoactive substance use need to be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms predominantly consist of delusions and hallucinations. 1,2 Green et al 3 examined 38 children with schizophrenic disorder who were younger than 12 years of age, and indicated that catatonia or other grossly disorganized behavior was present in 31.6% of the cases. In an Indian study by Thakur et al, 2 5.5% of the entire sample and 17.7% of the patients with affective and nonaffective psychotic disorders had at least two signs of catatonia.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of catatonia in psychiatric conditions other than schizophrenia and major mood disorders, specifically in the context of autism and other neurodevelopmental disorders. Catatonia not infrequently occurs in these disorders in the absence of major mood or other diagnosable psychotic disorders (Thakur et al, 2003;Dhossche et al, 2007;Ghaziuddin et al, 2012). The occurrence of catatonia in autism and other developmental disorders has important prognostic and treatment implications.…”
Section: A Residual Category Of Catatonia Not Otherwise Specified Wilmentioning
confidence: 99%